Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1097/jom.0b013e31815cff4b
|View full text |Cite
|
Sign up to set email alerts
|

Employees With Fibromyalgia: Medical Comorbidity, Healthcare Costs, and Work Loss

Abstract: • Compare prevalence rates of common comorbid conditions in employees diagnosed as having fibromyalgia (FM) or osteoarthritis (OA).• Identify trends in the use of medical care and prescription drugs by employees having FM or OA, as compared to control subjects.• Contrast total dollar costs and their components-medical costs, drug costs, and indirect costs of time lost from work-in employees with FM, those with OA, and control employees having neither of these disorders. ($10,199) approached OA costs ($10,86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
186
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(205 citation statements)
references
References 21 publications
18
186
0
1
Order By: Relevance
“…Consistent with previously published U.S. studies, 6,12,13 this study demonstrated that fibromyalgia is associated with substantial direct and indirect costs to payers, patients, and society. This study also demonstrated that costs are higher for patients with worse fibromyalgia severity.…”
Section: ■■ Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Consistent with previously published U.S. studies, 6,12,13 this study demonstrated that fibromyalgia is associated with substantial direct and indirect costs to payers, patients, and society. This study also demonstrated that costs are higher for patients with worse fibromyalgia severity.…”
Section: ■■ Discussionsupporting
confidence: 80%
“…Previous research has shown that a majority of patients with fibromyalgia seek care from primary care and other physicians; less than 20% seek care from rheumatologists. 12,17 These physician specialties were selected because they represent 4 specialties that treat fibromyalgia in the United States.…”
Section: Methods Study Designmentioning
confidence: 99%
See 3 more Smart Citations